Metodología para efectuar mediciones de calidad del servicio eléctrico en baja tensión. - Curipoma Quizhpe, Galo Israel (2017)
The present work develops a methodology to carry out measurements of electric power quality in low voltage, to program the network recording equipment, to install it, to export the data and to make calculations of the quality parameters of the product. For the calculation of these parameters an algorithm was made that allows the extraction of the database and the calculation of automatic form. For this purpose national and international norms have been considered as well as bibliography and methodologies that are related to the thematic approach. The methodology is developed for different types of energy quality recorders: Fluke, Topas 1000 and PQBox 100, which are the most common in our environment. The algorithm developed is general and can be applied to different load registers, although the order in which the data is exported must be taken into account, a situation explained in detail in the present. To validate the research project is used the electrical network recorder equipment FLUKE 1744, which is available in the Faculty of Energy Industries and Non-Renewable Natural Resources of the National University of Loja, with which measurements were made on the transformer Three-phase 50 kVA N °. 18213, to provide electricity to the laboratory building. The measurements were carried out in a period of seven days with an interval of 10 minutes, according to the recommendations issued in Regulation No. CONELEC¬_004 / 01. The measurement records are used in the methodology developed by inserting in a dynamic spreadsheet, to evaluate the quality of the low voltage product automatically. Analyzing the results it is determined that they are favorable since all the quality parameters are within the limits allowed according to the Regulation, obtaining for Phase A the following results: the limit of the voltage level is of ± 10% being the value census - 1.3% (125.56 V- meets); Flicker severity level not greater than 1 p.u. (0.29 p.u.-meet); Harmonic distortion of voltage not exceeding 8% (1.74% - complies) and the limit of the power factor not greater than 0.92 (0.95-complies), voltage harmonics of the order 2 to 40 are within the limits Established. Similar analysis can be performed for phase B and C.